Assessment of Vitamin B12 Status and Associated Factors among Hemodialysis Patients in Western Libya: A Multicenter Study - Abousouh, Ahmed; Aghali, Nanah; Saeid, Wisal; Owais, Aya; Albadrani, Moudah; Masoud, Amira (Sharwes Scientific Journal, 2026)
This study aimed to evaluate serum Vitamin B12 levels among hemodialysis patients in Western Libya, and to investigate the comprehensive association between these levels and various factors, including demographic data, clinical variables (such as dialysis duration and metformin use), dietary habits, and the prevalence of clinical symptoms like fatigue and mood changes. This cross-sectional study was conducted on 80 patients across three centers (Nalut, Zintan, and Tripoli) between June to December 2025. Serum Vitamin B12 was measured using Chemiluminescent Immunoassay (CLIA) on the Snibe Maglumi 800 analyzer. The results showed that 12.5% of patients had a deficiency, 51.2% had normal levels, and 36.3% showed elevated levels (>900 pg/mL). Dietary supplementation was the most significant factor linked to B12 levels (P = 0.000). Significant variations were found between the three centers (P = 0.020), with Kidney dialysis center at Nalut Central Hospital showing the lowest deficiency rates. Importantly, the results showed no statistically significant correlation between B12 levels and clinical symptoms or metformin use, suggesting that symptoms in these patients may stem from other uremic factors. In conclusion, although supplementation effectively reduces deficiency, a high percentage of patients exhibit laboratory hypervitaminosis. This elevation may suggest the presence of functional vitamin B12 deficiency, necessitating a more precise diagnostic approach.